Circular microstrip antenna with defected ground structure for bandwidth enhancement at 2.4 GHz - Muhammad Nur Fadly; Deri Latika Herda; Popy Maria (Geuthèë Institute, 2026)
This study proposes an optimized circular microstrip patch antenna integrated with a stepped-slot Defected Ground Structure (DGS) for 2.4 GHz WLAN applications. The objective of this work is to improve the bandwidth and gain performance of conventional microstrip antennas, which are typically limited by narrow bandwidth and low radiation efficiency. The main contribution of this study is the development of a novel stepped-slot DGS configuration combined with a circular patch geometry to achieve simultaneous enhancement of bandwidth and gain. The proposed antenna is designed on an FR-4 substrate with a dielectric constant of 4.3 and a thickness of 1.6 mm, and analyzed using CST Microwave Studio. A parametric optimization of the DGS dimensions is performed to obtain optimal antenna performance. Simulation results show that the bandwidth increases significantly from 70.4 MHz to 298.8 MHz, representing more than a fourfold improvement. In addition, the antenna gain improves from 2.72 dBi to 3.87 dBi after the implementation of the DGS structure. These results confirm that the proposed stepped-slot DGS effectively enhances impedance bandwidth and radiation performance without increasing antenna complexity. Therefore, the proposed antenna is suitable for practical WLAN applications requiring compact size and improved performance. The findings of this study also provide useful insights for the design of high-performance microstrip antennas using DGS techniques in future wireless communication systems.